Lung Metastasis from Perineal Leiomyosarcoma: A Case Report and a Review of the Japanese Literature. (5th March 2013) - Itoga, Masamichi; Ito, Wataru; Ueki, Shigeharu; Takeda, Masahide; Moritoki, Yuki; Kobayashi, Yoshiki; Chihara, Mami; Suzuki, Naoshi; Sasaki, Hideto; Chihara, Junichi
Abstract : Pulmonary metastasis from leiomyosarcoma is rare and its clinical management is challenging. A single lung metastasis from a perineal leiomyosarcoma occurred in a 79-year-old woman. Five months after resection of the lung metastasis, a new metastatic tumor developed in the contralateral lung. Since the patient did not desire to receive hospitalized treatment, TS-1 (an oral agent consisting of a combination of tegafur, gimeracil, and oteracil potassium) therapy was started on an outpatient basis. The lung metastasis has been successfully controlled for at least 17 months with excellent tolerability. The clinical features and the treatment of this case are discussed.